IMPLEMENTATION OF THE SIMERAK LANGKAT APPLICATION IN REPORTING THE PHYSICAL AND FINANCIAL REALIZATION OF THE APBD OF LANGKAT REGENCY - Khoirul Ma’arif; Rudi Salam Sinaga; Marlon Sihombing (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the implementation of the SIMERAK Langkat application in reporting the physical and financial realization of the APBD of Langkat Regency and to identify the factors that hinder its implementation. This study uses a qualitative method with a descriptive approach. Informants were selected purposively from application administrators, development data managers, and related parties at the regency level. Data were collected through in-depth interviews, documentation, and observation, then analyzed using an interactive data analysis model which includes data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of SIMERAK Langkat has been running quite effectively, but has not been optimal and has not been evenly distributed across all regional apparatuses. From the aspect of policy logic, policy objectives have been formulated clearly, application functions are relevant to reporting needs, and the system is relatively easy to use. However, its effectiveness is still constrained by the absence of an implementation roadmap, limitations of adaptive features, disparities in digital literacy, and the application not yet being integrated with SIPD. From the aspect of the policy environment, regulatory and leadership support is considered adequate, but disparities in technological infrastructure, limited capacity-building budgets, and the absence of detailed technical guidelines cause policy implementation to be uneven. From the aspect of implementor capability, implementors have sufficient basic competence and are supported by coordination mechanisms, but variations in capability, limited human resources, staff rotation without consideration of technical competence, and the absence of a reward and punishment system weaken reporting consistency. This study concludes that the success of implementing SIMERAK Langkat is largely determined by the alignment between policy design, institutional environmental support, and implementor capacity. Optimizing implementation requires strengthening strategic planning, refining technical regulations, equalizing resources, improving digital literacy, and integrating the system with SIPD.